As construções do materno em contextos de pobreza e vulnerabilidade psicossocial: contribuições para uma clínica do cuidado materno-infantil - Dauer, Érika Teles (2021)
This work has its origins in clinical practice with the families served by the Instituto da Primeira Infância (Iprede), who, in their majority, are part of the Brazilian poverty and psychosocial vulnerable social scenario, which may lead to restrictions and deprivations to their right of freedom and in the fulfillment of their fundamental needs. Faced with the initiative of setting up a group with the mothers, it became evident how the dimension of their sexuality offers a measure to the provision of care that is essential to mother-infant health. However, the complexity of this task increases in situations where the mothers need to be constantly involved in crucial issues for their survival, which may even lead to the development of trauma when they experience conditions of helplessness, deauthorization, and subjective disorganization. Through a bibliographic methodological path, based on inner thoughts of the intersubjective psychoanalytic perspective, the constructions of the maternal in the contexts of poverty and psychosocial vulnerabilities are investigated, to contribute to a clinic of mother-infant care. Ferenczi and Winnicott's theorizations were a starting point for the understanding of human nature based on object relations, highlighting the role that the mother and the family play in the infant's psychic constitution and development. The presence of the other may reach a potential facilitator or traumatic to subjectivity, subject to how the link between the individual and his primary caregiver is established. In our study, the relation of mother-infant care was an important foundation for establishing a clinic oriented towards a singularity of the experience and its reframing, working from a practice that offers recognition and provides the elaboration of expressions of suffering, pain, and malaise, taking account of the different forms of individual and community organization. In this way, therapeutic approaches should reconstruct the bases of maternal care, proceeding in the manner of a loving mother who presents the world bit by bit to the baby and enabling the patient to (re) live reliable experiences. Regarding the context of our investigation, through the offer of help and security to deal with the disproportion of the social environment, clinical practices may encourage the creation of alternative paths to introjection, as well as the construction of new alternatives and Life forms.